Analysis of Aircraft Movement Monitoring by Apron Movement Control Officers Due to the Absence of Lead In Markings at the Apron Area at Bandung's Husein Sastranegara International Airport - Ichyaan Perwira Jati; Febriansyah Ignas Pradana (CV. Rayyan Dwi Bharata, 2023)
Bandung's Husein Sastranegara International Airport does not have a Lead in marking in the Apron area and is one of the factors causing aircraft that will park to often leave the parking stand center line and have an impact on other aircraft that will park at the parking stand next to it. Apron Movement Control (AMC) officers play an important role in overseeing the movement of aircraft when they are going to park towards the parking stand because there is no Lead in marking on the apron area. The purpose of this study was to find out how the supervision of aircraft movements by Apron Movement Control (AMC) officers was due to the absence of Lead-in markings on the apron area and the impact of not having Lead-in markings on the Apron area at Husein Sastranegara International Airport, Bandung. This study uses a qualitative approach. The data used in this study is the result of interviews, observations, and documentation at the Apron Movement Control (AMC) unit of Husein Sastranegara International Airport, Bandung. The informants in this study were Apron Movement Control (AMC) officers. Observations were made by observing the Apron Movement Control (AMC) unit, and for documentation in this study, namely by taking pictures of events that occurred in the field. The results in this study are that Apron Movement Control (AMC) officers supervise by going directly to the field and ensuring that marshaller officers are in position for the aircraft to be parked, besides that Apron Movement Control (AMC) officers add at least one wingman for safety and safety in flight activities is maintained. Bandung's Husein Sastranegara International Airport does not have a Lead in marking on the apron area, which is one of the factors why planes often leave the centerline parking stand markings.